Co-Al and Mn-Fe Catalytic Steam Reforming of CH3OH to H2. Issue 1 (1st January 2022) - Li, Zehao; Zhang, Huili; Dewil, Raf; Deng, Yimin; Li, Shuo
Abstract: Catalytic production of hydrogen by steam methanol reforming (SMR) is an attractive option for specific applications in fuel cells, decentralized generation of H2 or localized boosting of the energy content of digestion gas. Supported metal catalysts integrate the endothermic methanol steam reforming with the exothermic Boudouard reaction. The paper reviews the fundamentals of SMR, develops 2 self-made, cheap and efficient catalysts, and demonstrates that high H2 yields with low CO and CO2 by-product formation. Present methanol reformers are mostly of the packed bed type which suffer from problems of temperature gradients within the catalyst bed and a slow response during start up and transients. In using a vibrated fluidized bed of the micron-size catalysts, a uniform bed temperature is achieved. More than 600 L/hr of hydrogen can be generated at methanol conversions in excess of 95%. A too high space velocity in the catalytic bed significantly reduces the methanol conversion, however without affecting the H2 yields. The assessed systems clearly merit pilot plant research.